Synthesis of 2-Halo-3-Formylindoles via Vilsmeier–Haack Haloformylation Reaction of Oxindole - Peng Zhao; Mingyu Jiang; Jiahui Li; Juan Feng; Shiyi Tang; Pengluo Wei; Hua Zhang (Journal of Chemistry, 2025)
A series of 2-halo-3-formylindole molecules were synthesized via Vilsmeier–Haack haloformylation reaction of N-Boc-oxindole with POCl3 or POBr3 and DMF, which are free from the use of catalyst and solvent. Moreover, through several simple postprocessing steps, corresponding adducts can be readily transformed to Tenidap analog intermediate. The feasibility of gram-scale experiments proved that the methodology has the potential to be scaled. In addition, a possible reaction mechanism was proposed based on control experiments.